2014
DOI: 10.1371/journal.pone.0090161
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Changes in Serum 25-Hydroxyvitamin D during Pregnancy and Lack of Effect on Thyroid Parameters

Abstract: Background & AimsTo explore vitamin D status and its dynamic changes during pregnancy in women living in Northeast China. The association between 25-hydroxyvitamin D and serum calcium, phosphate and parathyroid hormone was studied. Because vitamin D deficiency or thyroid dysfunction/autoimmunity during pregnancy may lead to similar adverse events, the relationship between 25-hydroxyvitamin D and thyroid parameters was investigated.MethodsSerum samples of 50 women (aged 22 to 36 years) were selected retrospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 62 publications
3
16
0
Order By: Relevance
“…In agreement with our findings, Marwaha et al (24) have shown no change in 25(OH) D concentrations with progression of pregnancy which could partly be explained by the food products that are not fortified with vitamin D and the absence of current guidelines on recommending mandatory vitamin D supplementation during pregnancy. In a study by Zhao et al (25), the mean level of 25(OH)D in the second trimester was significantly higher than the one in the first trimester and equivalent to the one in the third trimester. Our results are compatible with the recent study which reported high prevalence of severe vitamin D deficiency [25(OH) D<10 ng/mL] (45.6%) among pregnant women in Turkey (26).…”
Section: Discussionmentioning
confidence: 84%
“…In agreement with our findings, Marwaha et al (24) have shown no change in 25(OH) D concentrations with progression of pregnancy which could partly be explained by the food products that are not fortified with vitamin D and the absence of current guidelines on recommending mandatory vitamin D supplementation during pregnancy. In a study by Zhao et al (25), the mean level of 25(OH)D in the second trimester was significantly higher than the one in the first trimester and equivalent to the one in the third trimester. Our results are compatible with the recent study which reported high prevalence of severe vitamin D deficiency [25(OH) D<10 ng/mL] (45.6%) among pregnant women in Turkey (26).…”
Section: Discussionmentioning
confidence: 84%
“…As mentioned previously 25(OH) D status is Influenced by many factors [2,11,44] one of these factor is thyroid hormones changes by fetus action causing depletion of TSH, FT4 and FT3 leading to various problems such as placental abruption, miscarriage, fetal growth retardation [49]. Other studies recommended vitamin D supplementation during pregnancy [8,12,25].…”
Section: Discussionmentioning
confidence: 99%
“…Risk of heart disease and diabetes and their diseases .Vitamin D deficiency and/or VDRs gene polymorphism were associated with many kinds of autoimmune disorders, including type 1 diabetes mellitus, erythematosus systemic lupus, multiple sclerosis rheumatic arthritis [4][5][6][7]. It was reported that vitamin D deficiency associated with autoimmune diseases necessary and supplementation prevents the onset and/ or development of these autoimmune diseases [10,11] which is needed for development of skeletal muscle due to involvement in calcium homeostasis [2,12]. Therefore understanding sources of vitamin D supplementation is vital to reduce risk on mother and fetus.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations